Sekularisasi Sinyal Keagamaan Pada Pasar Multikultural: Model Jalur Ganda Konsumsi Halal Di Indonesia - M. Afif Shahputra Zen; Saparuddin Siregar; Sugianto Sugianto; Muhammad Habibi Siregar (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Provinsi Sumatera Utara, 2026)
This study aims to deconstruct the psychological architecture of consumer preferences for halal products within a multicultural market transitioning toward a mandatory certification regime. Amidst the theoretical schism between religious approaches (Theory of Planned Behavior) and utilitarian perspectives (Lancaster’s Theory), this research proposes an integrative model to explain how a single religious symbol acts as a driver for consumption across diverse faith groups simultaneously. Employing a Mixed-Methods Sequential Explanatory design, this study analyzed data from 182 respondents in Medan City using Partial Least Squares Structural Equation Modeling (PLS-SEM) with Multi-Group Analysis (MGA), followed by a qualitative deepening through Reflexive Thematic Analysis of 25 informants. The MGA results reveal a sharp and statistically significant behavioral divergence. In the Muslim group, the direct pathway from religion to preference is substantial (β = 0.293), driven by a mechanism of